2011
DOI: 10.1016/j.jss.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the JNK Signaling Pathway Potentiates the Antiproliferative Efficacy of Rapamycin in LS174T Colon Cancer Cells

Abstract: Taken together, these results show that rapamycin-induced JNK phosphorylation and activation reduces the antitumor efficacy of rapamycin in LS174T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…In both PEL cell lines, beside the induction of BiP, we found that proteasome inhibition by bortezomib determined a slight IRE1α upregulation (Figure 1A). Finally, JNK phosphorylation was analyzed, since IRE1 can activate, among other molecules, JNK that, in turn, may regulate cell survival [36]. We found JNK1/2 phosphorylation by bortezomib in both BC3 and BCBL1 cells (Figure 1A).…”
Section: Resultsmentioning
confidence: 95%
“…In both PEL cell lines, beside the induction of BiP, we found that proteasome inhibition by bortezomib determined a slight IRE1α upregulation (Figure 1A). Finally, JNK phosphorylation was analyzed, since IRE1 can activate, among other molecules, JNK that, in turn, may regulate cell survival [36]. We found JNK1/2 phosphorylation by bortezomib in both BC3 and BCBL1 cells (Figure 1A).…”
Section: Resultsmentioning
confidence: 95%
“…Notably, rapalogs mediated eIF4E phosphorylation was dependent on Mnk (MAP kinase interacting kinase) and the inhibition of Mnk increased rapamycin-mediated growth inhibition [97]. Finally, it has also been reported that rapamycin-activated JNK signaling pathway in colon cancer cells plus combined JNK and mTOR inhibition had additive anti-tumor effects [99]. Future studies will explore the relevance of rapalogs mediated eIF4E or JNK activation in a clinical setting.…”
Section: Mtor and Cancer; What We Have Learned From Basic Researchmentioning
confidence: 99%
“…Numerous studies have documented that rapamycin may alter the activity of MAPKs including JNK, Erk1/2 and/or p38 under various conditions, thus affecting cell proliferation, survival and apoptosis (Benoit et al, 2011; Hahn et al, 2005; Huang et al, 2003; Kato et al, 2013; Kawasaki et al, 2010; Shi et al, 2005). Our previous studies have identified that Cd activates JNK, Erk1/2, and p38, but only JNK and Erk1/2 participate in Cd-induced apoptosis in neuronal cells (Chen et al, 2008b).…”
Section: Resultsmentioning
confidence: 99%
“…We have also revealed that Cd induction of ROS activates Erk1/2 and JNK pathways leading to apoptosis in neuronal cells (Chen et al, 2008a). However, of note, some data have documented that rapamycin affects the activity of JNK, Erk1/2 and p38 under different conditions (Benoit et al, 2011; Hahn et al, 2005; Huang et al, 2003; Kato et al, 2013; Kawasaki et al, 2010; Shi et al, 2005). This prompted us to ask whether and how rapamycin blocks Cd-induced mitochondrial ROS activation of JNK, Erk1/2 and p38 pathways, involved in rapamycin protection against Cd neurotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation